Ecosystem-based fisheries management (or 'triple bottom line') assessments of the western rock lobster resource: Is there an optimal target for fishing?. (August 2018) - Caputi, Nick; de Lestang, Simon; How, Jason; Trinnie, Fabian; Fletcher, Warrick (Rick)
Abstract: Ecosystem-based fisheries management (EBFM) is often termed triple bottom line because it takes into account ecological, economic and social criteria. Effective implementation of EBFM requires development of appropriate governance structures for decision-making processes and management, so governance effectiveness and efficiency can be regarded as the fourth element in a 'quadruple bottom line.' Few fisheries have explicitly considered all four criteria within their resource assessments and harvest strategies. Furthermore, as some of these objectives may be in competition (e.g. employment levels, profit), a simultaneous evaluation of these criteria is required to identify the optimal level of fishing to deliver the best overall community outcome. The western rock lobster, Panulirus cygnus, resource in Western Australia is used as an EBFM case study by evaluating: sustainability of target species and effects on ecosystem and protected species; economics of the fishery; effect on employment, coastal communities and quality of recreational fishing; and governance effectiveness including explicit sectoral catch allocations, and the efficiency of monitoring and compliance systems. In 2010 the fishery moved from effort-controlled maximum sustainable yield (MSY) to a quota-controlled, maximum economic yield (MEY) system. This study explicitly examined how different levels of harvesting across the MSY to MEY range affected each of ten EBFM criteria. We confirmed that these individual objectives were maximised at different total allowable commercial catches. However an example is provided for weighting of objectives from a possible management perspective that identified the upper end of the MEY range as likely to generate the optimum outcome for this fishery.